2012
DOI: 10.1177/0961203311429550
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant immunization induces high levels of pathogenic antiphospholipid antibodies in genetically prone mice: another facet of the ASIA syndrome

Abstract: Adjuvants may induce autoimmune diseases in susceptible individuals, a phenomenon recently defined as autoimmune/inflammatory syndrome induced by adjuvants (ASIA). Patients with both antiphospholipid antibodies (aPL) and the genetic coagulopathy factor V Leiden (FVL) are frequently found. We therefore evaluated whether adjuvant can induce aPL in heterozygous FVL mice. aPL were measured in naïve mice and at 1 and 5 months after immunization with either complete or incomplete Freund's adjuvant (CFA, IFA) in FVL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…This datum is consistent with both evidence from clinical case reports [30,103,[105][106][107][108][109][110] and data from murine models where different adjuvants, such as Alum and MF59 [111][112][113][114][115] were characterised by several mechanisms of action.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…This datum is consistent with both evidence from clinical case reports [30,103,[105][106][107][108][109][110] and data from murine models where different adjuvants, such as Alum and MF59 [111][112][113][114][115] were characterised by several mechanisms of action.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…The most reasonable explanation for this late and prolonged elevation of aPL antibody levels in FVL Q/Q mice is that of an ongoing process, such as the chronic exposure of the immune system to activated components of the clotting system, which include β 2 -GPI. This is in line with our recent publication describing spontaneous development of specific pathogenic aPL (β 2 GPI-dependent) autoantibodies in genetically hypercoagulation-prone FVL mice immunized with adjuvant alone [34]. Interestingly, adjuvant-immunized FVL mice exhibited hyperactivity behavior compared with non-immunized FVL mice, which correlated with the autoantibody level [34].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, regarding immunologic effects, epidemiological studies have suggested an association of Thimerosal and patch-test sensitivity; countries that eliminated Thimerosal from vaccines such as Austria, Denmark, Poland, and the USA [26] observed a decrease in Thimerosal patch-test reactions. Moreover, both experimental [27] and clinical [28] studies have addressed autoimmune (autoinflammatory) syndrome induced by adjuvants (ASIA) in association with some adjuvanted vaccines. Although this emerging information is not part of the AEFI recording system the collected data are nevertheless shaping perceptions among health workers and stakeholders.…”
Section: Discussionmentioning
confidence: 99%